(untitled) (International Journal of Occupational Safety and Health, 2026)
Introduction: Burnout and dehumanization are frequent psychological phenomena in healthcare environments, particularly among nurses. While dehumanization may serve as an adaptive mechanism to manage emotional strain and enhance clinical efficiency, excessive or prolonged exposure can lead to self-dehumanization and disrupt nurse–patient relationships, ultimately impairing the quality of care. Methods: A cross-sectional study was conducted among 78 volunteer nurses employed in intensive care units [ICUs] of Evangelismos General Hospital in Athens, Greece. Data were collected using three validated questionnaires based on the Oldenburg Burnout Inventory and the Dehumanization and Mechanistic Self-Dehumanization scales developed by Katerina Roupa. Statistical analyses included Mann–Whitney, Kruskal–Wallis, and Spearman’s rho tests, with the significance level set at 0.05. Results: Most participants were female (67.9%) and over 40 years old (55.2%). Low burnout levels were found in 76.9% of participants, moderate in 15.4%, and high in 7.7%. Higher burnout levels were observed among nurses with lower educational backgrounds, permanent contracts, one or two children, and fewer working hours. Male nurses demonstrated higher dehumanization and self-dehumanization scores than females. Work exhaustion was associated with males having 3–10 years of experience. A significant negative correlation was found between self-dehumanization and burnout. Additionally, nurses who tended to dehumanize their patients were more likely to self-dehumanize. Conclusion: Although dehumanization and self-dehumanization may function as emotional regulation strategies against burnout, they have detrimental implications for nursing care and therapeutic relationships. Preventive interventions should aim to balance emotional resilience with patient-centered care. Keywords: Burnout, Dehumanization, Nurses, Occupational Stress, Self-Dehumanization